Effects of the Iceland plume on Greenland's lithosphere: New insights from ambient noise tomography - Antonijevic, S.K.; Lees, J.M. (Elsevier B.V., 2018)
Ambient noise tomography is used to image Greenland's lithosphere, which passed over the Iceland plume between ∼70 and ∼40 Ma. Cross-correlations from 21 stations from GLISN seismic network were used to invert for 2-D Rayleigh wave phase velocity maps for 14 periods between 8 and 40 s. We find that Rayleigh wave phase velocities substantially vary across Greenland, with slow velocities coinciding with NW-SE trending Iceland plume track. In east Greenland the detected velocity reduction at longer periods (33–40s) reflects substantially thinned lithosphere, thermally ablated by the plume. From the east, the reduced velocities shift NW at shorter periods (12–20s), indicating shallowing of the plume-related slow anomaly. In north-central Greenland, the reduced velocities appear in the proximity of the plume ∼60 Ma, reflecting lithospheric weakening in the presence of residual heat that still persists within the lithosphere. Our results provide important new constraints on variations in the seismic velocity structure of Greenland's crust and uppermost mantle, revealing prolonged effects of the mantle plume on the overpassing craton.